The potential of carbon footprint reduction of a mid-rise residential building in Sarawak / Nurdiyanah Yaman and Ahmad Faiz Abd Rashid - Yaman, Nurdiyanah; Abd Rashid, Ahmad Faiz (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2021)
Carbon emission is released into the atmosphere as the result of various activities due to rapid urbanisation and thus contributed to global warming and climate change. The government has taken various initiatives to reduce the impact, including from the construction industry in order to support the carbon footprint reduction of 40% as pledged by the Prime Minister. Various strategies, such as the Malaysian Carbon Reduction and Environmental Sustainability Tool (MyCREST), have been established to promote green building development in Malaysia. Recent studies suggested that the selection of sustainable materials can reduce the overall carbon emission of a building, but the cost has been identified as the main barriers. This paper aims to analyse the potential of carbon footprint reduction by using sustainable material in mid-rise residential building and subsequently to evaluate the cost implication. The impact of the conventional and the selected sustainable materials was assessed using data from the MyCREST tool while the data for cost analysis were taken from various sources of cost data such as JKR Rates online (RATOL), JKR Sarawak Schedule of Rates (SOR), and previous research. The results show that the sustainable materials such as 30% of Blast Furnace Slag (BFS) concrete mixture, Aerated Autoclaved Concrete (AAC) block, and recycled steel roof truss has the potential to reduce the carbon emission. The findings also show that sustainable materials are slightly cheaper than the conventional materials except for the AAC block and clay roof tiles. Therefore, the potential of carbon emission reduction approach by using MyCREST as a guideline tool can assist in the reduction of the environmental impact of buildings.